Bioimpedance: Innovative Approach in Nephrology and Autoimmune Diseases - Ioannis Griveas (Archives of Clinical Nephrology - Peertechz Publications, 2016)
The composition of the human body is considered a useful diagnostic tool in many medical specialties. The recognition of changes in nutrition and hydration of patients is useful in nephrology and in particular in chronic kidney disease where malnutrition and over hydration are conditions that affect the prognosis of these patients. Furthermore, the use of 'traditional' diagnostic tests based on clinical examination and biochemical tests often lead to inaccurate results [1,2].